[Translated article] Cutaneous and Mucosal Conditions Associated With Cocaine Use - A. Sánchez-Puigdollers; M. Just-Sarobé; L. Pastor-Jané (Elsevier, 2023)
Cocaine and some of its main adulterants, such as levamisole, can cause multiple cutaneous and mucosal manifestations, including ischemic complications, neutrophilic dermatoses, midline destructive lesions, and vasculitis associated with antineutrophil cytoplasmic antibodies (ANCAs). Striking systemic symptoms are generally not seen. In all these conditions, positive test results may be observed for antinuclear antibodies, antiphospholipid antibodies, and various ANCAs, sometimes with characteristic staining patterns. Histology typically shows vascular changes, such as leukocytoclastic vasculitis, necrotizing vasculitis, and thrombi. We review the clinical, serologic, and histologic features of cutaneous and mucosal conditions associated with the use of cocaine and also look at pathophysiologic mechanisms, differential diagnoses, and treatments. Resumen: El consumo de cocaína, junto con algunos de sus adulterantes más frecuentes como el levamisol, puede provocar múltiples procesos cutáneos y mucosos, ya sean de índole isquémico, dermatosis neutrofílicas, lesiones destructivas de la línea media y vasculitis asociadas a ANCA, entre otros. Generalmente no se asocia clínica sistémica llamativa. Todos estos cuadros pueden presentar anticuerpos antinucleares, antifosfolípido y contra distintos antígenos de los neutrófilos, en ocasiones con un patrón característico. El estudio histológico suele mostrar cambios vasculares, como vasculitis leucocitoclástica, necrosis de la pared y trombos. En este artículo revisamos las características clínicas, serológicas e histológicas de estas entidades, junto con los mecanismos fisiopatológicos implicados, el diagnóstico diferencial y su tratamiento.